ASSESSING THE LEVEL OF THE STUDENTS’ READING COMPREHENSION ABILITIES AND ITS DIFFICULTIES - Rahmah, Dita Aulia; Mistar, Junaidi (Premise: Journal of English Education and Applied Linguistics, 2023)
This study aimed to assess the student's reading comprehension level and the difficulties that the students faced in reading. The writer conducted this study at Senior High School 2 Pasuruan, especially the 11th-grade students in Language Programs. This study focused on the student's reading ability level and the difficulties that the students faced in reading. The writer used survey research designs in conducting this study. The participants of this study were 30 students. In collecting the data, the writer distributed closed-ended questionnaires, which consisted of 29 questions with a 4-point scale (always, sometimes, rarely, and never). The result showed that 47% of students faced many problems or difficulties understanding the reading text. While 37% of students sometimes found difficulties reading an English passage, 16% of the students who chose "rarely" indicated that the difficulty they faced was not challenging. In conclusion, it was found that many students still need help comprehending the text. The study implies that the influencing factors in reading must be addressed.